Implementasi Teknologi dan Internet Of Thing (IoT) Untuk Otomasi Penyiraman Tanaman Berbasis Telegram di SDN1 Triharjo - Humairoh Ratu Ayu; Sri Wahyu Suciyati; Hapin Afriyani; Dwina Nurizky Syahputri (Universitas Serang Raya, 2022)
SDN 1 Triharjo is committed to continuously improving student and school achievement, with a mission to create green and healthy schools. One of the standards that must be met to realize a green school is to take care of optical plants by making automatic plant sprinklers. School residents are still not aware of the importance of watering plants, because it will affect plant growth. Therefore, in this community service activity, assistance in the implementation of technology and internet of things (IoT) will be carried out for telegram-based plant watering automation. The direct involvement of teachers and students in implementing PkM activities is expected to increase the awareness of school residents to carry out environmental care behavior. The implementation of this activity is expected to be one of the added values for partner schools.